PENGARUH AKTIVITAS SUPERVISI KEPALA SEKOLAH TERHADAP PENINGKATAN PROFESIONALISME MENGAJAR GURU - Rijal Lubis, Alkausar Saragih (PUSKAPAD, 2022)
The school principal as a supervisor must be manifested in the ability of compiling, and implementing educational supervision programs, and utilizing the results. The ability to develop educational supervision programs must be realized in the preparation of class supervision programs, development of supervision programs for extra-curricular activities, development of library, laboratory and examination supervision programs. The aims of this research are as follows: (1) To obtain data and information about the supervision of school principals; (2) To obtain data and information on the professionalism of teachers at Perbaungan Dharma Utama High School; (3) To obtain data and information about the influence of the principal's supervision on teacher professionalism at SMA Dharma Utama Sukasari Perbaungan. The research hypothesis is: